1987
DOI: 10.1177/001872088702900203
|View full text |Cite
|
Sign up to set email alerts
|

A Psychophysiological Assessment of Operator Workload During Simulated Flight Missions

Abstract: Previous research has indicated that components of the event-related potential (ERP) may be used to quantify the resource requirements of complex cognitive tasks. The present study was designed to explore the degree to which these results could be generalized to complex, real-world tasks. The study also examined the relations among performance-based, subjective, and psychophysiological measures of operator workload. Seven male volunteers, enrolled in an instrument flight rule (IFR) aviation course at the Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(93 citation statements)
references
References 30 publications
6
84
0
3
Order By: Relevance
“…However, previous research (Kramer et al, 1987) found significant differences in P300 responses with a comparable sample size. Further, if P300 responses are to be used as an on-line index of mental workload for application in adaptive systems, they will need to provide robust measurements distinguishable without large sample sizes.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…However, previous research (Kramer et al, 1987) found significant differences in P300 responses with a comparable sample size. Further, if P300 responses are to be used as an on-line index of mental workload for application in adaptive systems, they will need to provide robust measurements distinguishable without large sample sizes.…”
Section: Discussionmentioning
confidence: 61%
“…Conversely, Kramer, Sirevaag, and Braune (1987) found that performance data (RT, accuracy) generated by an auditory detection task were not sensitive to changes in simulated flight task difficulty; however, peak amplitude for the P300 component was sensitive to manipulations in flight task difficulty. If sensitive to external task demands, ERP components have the potential advantage of not requiring an overt response by the participant (Mangun & Hillyard, 1995).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…This is further corroborated by the ERP pattern to the target stimuli. As in other dual task studies conducted with ERPs (Kramer et al, 1983(Kramer et al, , 1987Isreal et al, 1980), the amplitude of the P3b component to the targets in the secondary oddball task can serve as an indirect measure of processing demands of the primary ONG/RNG task (Kok, 2001). As the physical stimuli were identical for the RNG and ONG conditions, the reduced amplitude of the P3b during RNG suggests that more processing resources are taken up by this condition.…”
Section: Attentional Demandsmentioning
confidence: 74%
“…Generally, it is not an inherent property, rather it emerges from the interaction between the requirements of a task, the circumstances under which it is performed, and the skills, behaviors and perceptions of the operator. The operational and practical nature of the construct of human mental workload, in the last few decades, has been acquiring interest in Neuro-science, Physiology and even Computer science (Kramer and Sirevaag, 1987;Kantowitz, 1988;Donnell and Eggemeier, 1998;Young and Stanton, 2001). There is a wide application field (Donnell and Eggemeier, 1998;Tracy and Albers, 2006;Xie and Salvendy, 2000;Gwizdka, 2009a;Gwizdka, 2009b) and this new research domain may have an important impact in the future, above all in Human-Computer Interaction.…”
Section: Related Workmentioning
confidence: 99%